2018
DOI: 10.1039/c7ta09099d
|View full text |Cite
|
Sign up to set email alerts
|

Integrated perovskite solar capacitors with high energy conversion efficiency and fast photo-charging rate

Abstract: An integrated perovskite solar capacitor combining a perovskite solar cell and a supercapacitor is developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(72 citation statements)
references
References 59 publications
0
71
0
1
Order By: Relevance
“…The electrode materials are playing a vital role to enhance the energy density of SCs by increasing its operating potential window. The electrode materials of SCs should possess high catalytic activity, excellent electrical conductivity, extraordinary surface area, exclusive porous architecture, outstanding mechanical stability, and low production cost . Moreover, the fabrication of asymmetric SCs (ASCs) has recently drawn research interest among scientists, since it can integrate battery‐type Faradic electrode as energy sources as well as a capacitor‐type electrode as power sources to enhance the energy density of the SCs .…”
Section: Introductionmentioning
confidence: 99%
“…The electrode materials are playing a vital role to enhance the energy density of SCs by increasing its operating potential window. The electrode materials of SCs should possess high catalytic activity, excellent electrical conductivity, extraordinary surface area, exclusive porous architecture, outstanding mechanical stability, and low production cost . Moreover, the fabrication of asymmetric SCs (ASCs) has recently drawn research interest among scientists, since it can integrate battery‐type Faradic electrode as energy sources as well as a capacitor‐type electrode as power sources to enhance the energy density of the SCs .…”
Section: Introductionmentioning
confidence: 99%
“…Taking advantage of the bandgap tunability for perovskite materials, the open‐circuit voltage V oc for PSCs can reach over 1.0 V, which is suitable for high voltage photocapacitors. [ 42,43 ] Over the past several years, PSCs gradually became a competitive solar energy harvesting candidate in photocapacitors.…”
Section: Photorechargeable Supercapacitorsmentioning
confidence: 99%
“…PEDOT and carbon materials not only possess charge storage function in supercapacitors based on EDL capacitance or pseudocapacitance but also are employed in PSCs as carriers transporting layers. [ 42,44 ] Similar to DS‐photocapacitors, PEDOT or carbon materials were widely used as common electrode in PSCs based photocapacitors. As an example, a PEDOT‐carbon electrode was demonstrated to bridge the supercapacitor part and the perovskite solar cell part.…”
Section: Photorechargeable Supercapacitorsmentioning
confidence: 99%
“…Liu et al reported power packs that integrated an asymmetric MnO 2 -carbon SC with aP SC to achievea ne nergy-storage proportion of 76 % and an overall photoelectric conversion efficiency of 5.26 %, thus correspondingt oam aximum photocharging voltage of 0.96 V. [47] Recently,L iang et al achieved efficient and stable "photoelectrochemical-electricity" EC based on an all-inorganic perovskite solar capacitor. [35,48] The diagram for this PSC-based PS is presented in Figure 5a.T he all-inorganic CsPbI 3 ,w ith aw ide band gap, was employed as as olar absorber and the PSC provided a V oc as high as about 1.2 V; the corresponding J sc and PCE values were measured to be 7.3 mA cm À2 and 6.1 %, respectively.B enefiting from ah ighp hotocharging voltage, the PSC-based solar capacitor,w ith al ayereds tructure of nanocarbon/silica-gel electrolyte/nanocarbon, resulted in ah igh h overall , with amaximum value of 5.1 %.…”
Section: Three-electrode Pss Based On Pscsmentioning
confidence: 99%